English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

f(x) = 4x^2 - 4x + 11 for x = -4 ???

2007-03-30 05:06:00 · 5 answers · asked by chickiejam 1 in Science & Mathematics Mathematics

5 answers

substitute x = -4 into the function

f(-4) = 4.-4.-4 - 4.(-4) + 11
= 64 + 16 + 11
= 91

2007-03-30 05:09:26 · answer #1 · answered by Orinoco 7 · 0 0

4(-4)^2 -4(-4) + 11
=4*16+16 + 11
=64 +16 +11 = 91

2007-03-30 05:12:27 · answer #2 · answered by ironduke8159 7 · 0 0

f(-4) = 4(-4)^2 - 4(-4) + 11
=4(16) +16 + 11
=64 + 27
=91

2007-03-30 05:20:13 · answer #3 · answered by pritamgola 2 · 0 0

91

2007-03-30 05:15:34 · answer #4 · answered by Anonymous · 0 0

4(-4)^2-4(-4)+11=91

2007-03-30 05:11:48 · answer #5 · answered by dwinbaycity 5 · 0 0

fedest.com, questions and answers